2004
DOI: 10.4269/ajtmh.2004.70.72
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Effectiveness of Diagnostic Tests for Visceral Leishmaniasis

Abstract: We compared the validity of pancytopenia, the formol-gel test (FGT), the indirect fluorescence antibody test (IFAT), the direct agglutination test (DAT), and the rK39 dipstick test as diagnostic criteria for visceral leishmaniasis (VL) in Nepal. Between September 2000 and January 2002, 310 clinical suspects had a bone marrow aspirate, and if negative, a spleen aspirate smear examined for Leishmania donovani. Sensitivity and specificity of all tests were determined compared with parasitology and by latent class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
118
2
8

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(144 citation statements)
references
References 19 publications
16
118
2
8
Order By: Relevance
“…Additionally, the same location, the estimated direct cost of treatment with amphotericin B deoxycholate was USD 260.00 25 . Boelaert et al 26 estimated a direct cost of USD 150.00 for Glucantime ® treatment in Sudan. Vanlerberghe et al 27 reported that the estimated direct costs of diagnosis using a rapid test and treatment with N-methylglucamine antimoniate, amphotericin B, and liposomal amphotericin B deoxycholate in various endemic areas were USD 120.10, USD 111.10, and USD 537.50, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the same location, the estimated direct cost of treatment with amphotericin B deoxycholate was USD 260.00 25 . Boelaert et al 26 estimated a direct cost of USD 150.00 for Glucantime ® treatment in Sudan. Vanlerberghe et al 27 reported that the estimated direct costs of diagnosis using a rapid test and treatment with N-methylglucamine antimoniate, amphotericin B, and liposomal amphotericin B deoxycholate in various endemic areas were USD 120.10, USD 111.10, and USD 537.50, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…7 For CL, microscopy of skin smears and culturing parasites are associated with low sensitivity. 6 , 8 For VL a range of serological diagnostic techniques have been developed that are both sensitive and cost effective; the direct agglutination test (DAT) and the rK39 tests are extensively used in Asia and Africa 9 ; rK39 is also the diagnostic of choice for kala-azar elimination from South-East Asia. 10 , 11 However, antibodies detected by these tests can be found in the blood of infected patients for many months after the parasites have disappeared, making detection of active infection inaccurate; moreover, serological tests may not be used on immuno-compromised individuals.…”
Section: Introductionmentioning
confidence: 99%
“…This infection has several diverse clinical manifestations: cutaneous, mucosal and most notably visceral leishmaniasis, and is caused by Leishmania amazonensis, Leishmania braziliensis, and Leishmania donovani species. [1][2][3][4] An estimated 1.5 to 2 million new cases of leishmaniasis occurs each year in the world, which in the visceral manifestation is often fatal if untreated. [5][6][7][8][9] Unfortunately non-availability of satisfactory chemotherapeutic agents and failure to develop an effective Synthesis, X-ray Crystal Structure and Theoretical Calculations J. Braz.…”
Section: Introductionmentioning
confidence: 99%